All-solid-state metal lithium battery and preparation method thereof
By using the negative electrode of lithium carbon composite material, a carbon sintered porous skeleton containing carbon nanotubes and silver wires, and filled with lithium alloys and metal lithium, the problems of low energy density and solid electrolyte stability of lithium ion batteries are solved, and an all-solid metal lithium battery with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202311086038.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
The energy density of existing lithium-ion batteries is low, and there are dendrite, "dead lithium" and volume expansion problems when using solid electrolytes, which affects the stability and safety of the battery.
A negative electrode composed of lithium-carbon composite material, including a carbon sintered porous skeleton containing carbon nanotubes and silver wires, is used to fill the gaps of the skeleton to form a battery with high tensile strength and high energy density.
It has achieved a fully solid metal lithium battery with stable structure, high energy density and long cycle life. It is suitable for industrial production, and maintains the contact between the solid electrolyte and the negative electrode under relatively small pressure to stabilize the interface.
Smart Images

Figure CN119517948A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to an all-solid-state metal lithium battery and a preparation method thereof. Background Art
[0002] As a secondary battery, lithium-ion batteries are widely used in 3C, new energy vehicles and other fields. As people's requirements for equipment endurance continue to increase, the energy density of existing lithium-ion batteries (generally less than 250Wh / kg) cannot meet the demand for higher energy density, and it is urgent to improve the energy density of lithium-ion batteries.
[0003] The metal lithium anode has a low density (0.534g / cm 3 ), the highest theoretical capacity (3860mAh / g) and the lowest electrochemical potential (-3.04V VS. standard hydrogen electrode) have always been a research hotspot, providing the possibility for manufacturing the next generation of secondary batteries with high energy density (>300Wh / kg).
[0004] At present, liquid lithium-ion batteries need to use low-flash point, volatile electrolytes. When the battery has an internal short circuit or is subjected to mechanical impact, thermal runaway is prone to occur, leading to safety accidents. In addition, the electrolyte will also cause a decrease in the overall energy density of the battery. On the other hand, for the use of solid electrolytes, the amount of solid electrolytes can be reduced through solid electrolyte thin film technology, which can effectively reduce the overall weight of the battery and is suitable for the manufacture of high-energy-density metal lithium batteries. However, a common problem in systems using solid electrolytes is that the use of metal lithium negative electrodes will produce dendrite problems, "dead lithium" problems, and volume expansion problems.
[0005] In summary, it is of great significance to develop an all-solid-state metal lithium battery with high energy density and stable negative electrode using solid electrolyte. Summary of the invention
[0006] Based on the technical problems described above, the purpose of the present invention is to provide an all-solid-state metal lithium battery and a method for preparing the same. The all-solid-state metal lithium battery according to the present invention has a negative electrode composed of a lithium-carbon composite material with a stable structure and light weight, high energy density and long cycle life. The negative electrode composed of a lithium-carbon composite material used in the all-solid-state metal lithium battery has a higher tensile strength than pure metallic lithium, which is convenient for industrial production. The negative electrode composed of a lithium-carbon composite material is used in the all-solid-state metal lithium battery, which can maintain the contact between the solid electrolyte and the negative electrode under a relatively small pressure, making the interface between the negative electrode and the solid electrolyte more stable.
[0007] The inventors have completed the present invention after intensive and careful research.
[0008] According to one aspect of the present invention, there is provided an all-solid-state metal lithium battery, the all-solid-state metal lithium battery comprising:
[0009] positive electrode;
[0010] solid electrolyte; and
[0011] The negative electrode is composed of a lithium-carbon composite material, which includes a carbon sintered porous skeleton containing carbon nanotubes and silver wires, wherein the gaps in the carbon sintered porous skeleton are filled with lithium alloy and metallic lithium.
[0012] According to some preferred embodiments of the present invention, the positive electrode comprises one or more of an organic positive electrode material and an inorganic positive electrode material.
[0013] According to certain preferred embodiments of the present invention, the organic cathode material is selected from one or more of polypyrrole and its derivatives, polyacrylonitrile and its derivatives, and anthraquinone and its derivatives.
[0014] According to certain preferred embodiments of the present invention, the inorganic positive electrode material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobalt oxide, lithium manganese oxide (LiMn2O4, LiMnO2), lithium nickel oxide, lithium nickel manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, over-lithiated positive electrode, sulfur, carbon and oxygen.
[0015] According to certain preferred embodiments of the present invention, the solid electrolyte comprises one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.
[0016] According to certain preferred embodiments of the present invention, the metal lithium battery further comprises a packaging material.
[0017] According to certain preferred embodiments of the present invention, the metal lithium battery is a soft-pack battery, a cylindrical battery or a steel-shell battery.
[0018] According to certain preferred embodiments of the present invention, the silver wires are entangled by the carbon nanotubes and interspersed in the carbon sintered porous framework.
[0019] According to certain preferred embodiments of the present invention, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g.
[0020] According to certain preferred embodiments of the present invention, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0021] According to certain preferred embodiments of the present invention, the carbon nanotubes are multi-walled carbon nanotubes.
[0022] According to certain preferred embodiments of the present invention, the carbon nanotubes have a diameter ranging from 1 nm to 100 nm, preferably from 5 nm to 65 nm, more preferably from 7 nm to 48 nm, and a length ranging from 3 μm to 15 μm.
[0023] According to certain preferred embodiments of the present invention, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm.
[0024] According to certain preferred embodiments of the present invention, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
[0025] According to certain preferred embodiments of the present invention, based on 100% weight of the lithium-carbon composite material, the weight of the carbon nanotubes accounts for 2-75% by weight, preferably 7-55% by weight, and more preferably 11-46% by weight.
[0026] According to certain preferred embodiments of the present invention, based on 100% weight of the lithium-carbon composite material, the weight of the silver wire accounts for 0.5-25% by weight, preferably 1.2-18% by weight, and more preferably 3.5-14.5% by weight.
[0027] According to certain preferred embodiments of the present invention, based on the weight of the lithium-carbon composite material being 100%, the weight of the lithium alloy accounts for 2-57 weight %, preferably 3.6-48 weight %, and more preferably 5.4-34.5 weight %.
[0028] According to certain preferred embodiments of the present invention, based on the weight of the lithium-carbon composite material being 100%, the weight of the metallic lithium accounts for 2-95.5 weight%, preferably 10-87 weight%, and more preferably 21-75 weight%.
[0029] According to certain preferred embodiments of the present invention, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0030] According to certain preferred embodiments of the present invention, the thickness of the negative electrode is in the range of 1 μm to 200 μm, preferably 1 μm to 5 μm.
[0031] According to another aspect of the present invention, a method for preparing an all-solid-state lithium metal battery is provided, the method comprising the following steps:
[0032] (a) dispersing carbon nanotubes, silver wires, a binder and a cross-linking agent in a solvent to prepare a dispersion;
[0033] (b) treating the dispersion at high temperature to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires;
[0034] (c) adding a lithium alloy to molten metallic lithium to prepare a lithium melt containing the lithium alloy;
[0035] (d) immersing the carbon sintered porous skeleton containing the carbon nanotubes and the silver wires into the lithium melt containing the lithium alloy, so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton;
[0036] (e) taking out the impregnated carbon sintered porous skeleton from the lithium melt, casting an ingot and cooling it to obtain a lithium-carbon composite material;
[0037] (f) processing the lithium-carbon composite material into a negative electrode; and
[0038] (g) assembling a positive electrode, a solid electrolyte and the negative electrode to obtain the metal lithium battery.
[0039] According to some preferred embodiments of the present invention, the positive electrode comprises one or more of an organic positive electrode material and an inorganic positive electrode material.
[0040] According to certain preferred embodiments of the present invention, the organic cathode material is selected from one or more of polypyrrole and its derivatives, polyacrylonitrile and its derivatives, and anthraquinone and its derivatives.
[0041] According to certain preferred embodiments of the present invention, the inorganic positive electrode material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, over-lithiated positive electrode, sulfur, carbon and oxygen.
[0042] According to certain preferred embodiments of the present invention, the solid electrolyte comprises one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.
[0043] According to certain preferred embodiments of the present invention, the carbon nanotubes are multi-walled carbon nanotubes.
[0044] According to certain preferred embodiments of the present invention, the carbon nanotubes have a diameter ranging from 1 nm to 100 nm, preferably from 5 nm to 65 nm, more preferably from 7 nm to 48 nm, and a length ranging from 3 μm to 15 μm.
[0045] According to certain preferred embodiments of the present invention, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm.
[0046] According to certain preferred embodiments of the present invention, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
[0047] According to certain preferred embodiments of the present invention, the binder is selected from one or more of polyvinyl alcohol, polyvinylidene fluoride, polybutylene styrene, polystyrene, polycarboxycellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and its derivatives, monosaccharide or polysaccharide polymers.
[0048] According to certain preferred embodiments of the present invention, the crosslinking agent is selected from one or more of carbomer, benzoyl peroxide, diethylenetriamine, hydrated sodium borate, cellulose derivatives and isothiazolinone.
[0049] According to certain preferred embodiments of the present invention, the solvent is selected from one or more of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, lemon essence, alcohol, xylene, toluene cyclohexanone, isopropanol, ethyl ether, propylene oxide, methyl butyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol and ethylenediamine.
[0050] According to certain preferred embodiments of the present invention, the high temperature treatment comprises heating the dispersion at a temperature of 350° C. to 800° C. for 1 to 5 hours.
[0051] According to certain preferred embodiments of the present invention, the temperature of the molten metallic lithium is in the range of 200°C to 2500°C.
[0052] According to certain preferred embodiments of the present invention, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0053] According to certain preferred embodiments of the present invention, in step (a), the weight ratio of the binder, the cross-linking agent and the carbon nanotubes is (5-65):(2-25):(10-93).
[0054] According to certain preferred embodiments of the present invention, in the carbon sintered porous framework, the silver wires are entangled by the carbon nanotubes and are interspersed in the carbon sintered porous framework.
[0055] According to certain preferred embodiments of the present invention, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g.
[0056] According to certain preferred embodiments of the present invention, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0057] According to certain preferred embodiments of the present invention, the thickness of the negative electrode is in the range of 1 μm to 200 μm, preferably 1 μm to 5 μm.
[0058] According to certain preferred embodiments of the present invention, step (f) comprises subjecting the lithium-carbon composite material to at least one of cutting, melt coating, extrusion, flat pressing, roller pressing, and low-temperature crushing.
[0059] Compared with the prior art in this field, the metal lithium battery of the present invention has at least the following advantages:
[0060] 1. The lithium-carbon composite negative electrode contains carbon nanotubes, silver wires, and lithium alloys. The skeleton structure constructed by the three of them is more stable and the battery cycle life is long;
[0061] 2. The lithium-carbon composite negative electrode has a three-dimensional carbon nanotube skeleton, which can inhibit the growth of lithium dendrites and the volume expansion of the material;
[0062] 3. Carbon nanotubes are good conductors of electrons and ions. Whether in a liquid battery system or a solid-state battery system, metallic lithium can be preferentially deposited on the silver wire nucleating agent, thereby achieving uniform and dense deposition of metallic lithium on the entire multi-walled carbon nanotube skeleton;
[0063] 4. The three frameworks have obvious synergistic effects. The silver wire is interspersed in the multi-walled carbon nanotube framework and the surface is wrapped by carbon nanotubes. In addition, the carbon nanotube framework is also filled with lithium alloy. The carbon nanotubes and lithium alloy can lock the silver wire nucleating agent in a fixed position, making the electrochemical performance of the lithium-carbon composite material more stable.
[0064] 5. The all-solid-state metal lithium battery uses lightweight carbon material as the three-dimensional skeleton, and the battery energy density is high;
[0065] 6. The lithium-carbon composite negative electrode used in this all-solid-state lithium metal battery has a higher tensile strength than pure lithium ribbon and is suitable for industrial production;
[0066] 7. The all-solid-state lithium metal battery uses a negative electrode made of a lithium-carbon composite material, which can maintain the contact between the solid electrolyte and the negative electrode under low pressure, making the interface between the negative electrode and the solid electrolyte more stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 A scanning tunneling microscope (SEM) photograph of a carbon sintered porous framework containing carbon nanotubes and silver wires prepared in Example 1 of the present invention is shown;
[0068] Figure 2 A scanning tunneling microscope (SEM) photograph of the lithium-carbon composite material prepared in Example 1 of the present invention is shown; and
[0069] Figure 3 The cycle curves of the lithium metal soft-pack batteries prepared in Example 1 of the present invention and Comparative Example 3 are shown. DETAILED DESCRIPTION
[0070] The present invention will be described in further detail below in conjunction with specific embodiments. It will be appreciated that other embodiments are contemplated and may be implemented without departing from the scope or spirit of the present invention. Therefore, the following detailed description is non-restrictive.
[0071] Unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physicochemical properties should be understood as being modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0072] The present invention provides an all-solid-state metal lithium battery with high energy density and stable negative electrode. The present invention adopts a lithium-carbon composite negative electrode with stable performance. The composite negative electrode has a three-dimensional carbon nanotube skeleton structure, which can reduce local current density and reduce the generation of lithium dendrites; the lithium-carbon composite negative electrode contains a silver wire nucleating agent, which can induce uniform and dense deposition of metal lithium. The carbon nanotubes are wound around the silver wire nucleating agent to form a three-dimensional skeleton structure with stable structure. The nucleating agent in the lithium-carbon composite negative electrode will continue to expand and contract during the charging and discharging process, but due to the surface winding carbon nanotubes, the carbon nanotubes can adapt to the volume change of the silver wire nucleating agent, so that the silver wire is firmly fixed on the three-dimensional carbon nanotube skeleton; at the same time, the nucleating agent runs through the carbon nanotube network, and the multi-walled carbon nanotubes also have a certain limiting effect on the nucleating agent. The compound-type lithium alloy filled in the carbon nanotube skeleton has a relatively stable structure. Even if the metal lithium is pulled out, the remaining compound-type lithium alloy will not only play a structural supporting role for the multi-walled carbon nanotube skeleton, but also play a limiting role on the nucleating agent. The above three aspects ensure the structural stability of the lithium-carbon composite negative electrode. In addition, the all-solid-state metal lithium battery uses a negative electrode made of a lithium-carbon composite material, which can maintain the contact between the solid electrolyte and the negative electrode under a small pressure, making the interface between the negative electrode and the solid electrolyte more stable.
[0073] Specifically, the present invention provides an all-solid-state metal lithium battery, which comprises:
[0074] positive electrode;
[0075] solid electrolyte; and
[0076] The negative electrode is composed of a lithium-carbon composite material, which includes a carbon sintered porous skeleton containing carbon nanotubes and silver wires, wherein the gaps in the carbon sintered porous skeleton are filled with lithium alloy and metallic lithium.
[0077] There is no particular restriction on the material used for the positive electrode of the present invention. Preferably, the positive electrode comprises one or more of an organic positive electrode material and an inorganic positive electrode material. The organic positive electrode material is selected from one or more of polypyrrole and its derivatives, polyacrylonitrile and its derivatives, and anthraquinone and its derivatives. The inorganic positive electrode material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobaltate, lithium manganate, lithium nickelate, lithium nickel manganate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, over-lithiated positive electrode, sulfur, carbon and oxygen.
[0078] Preferably, the solid electrolyte comprises one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte. Specific examples of the materials listed above can be commercially available or prepared according to known methods.
[0079] Optionally, the metal lithium battery further comprises packaging materials, and the packaging method is at least one of a soft-pack battery, a cylindrical battery or a steel-shell battery.
[0080] Preferably, by controlling the preparation process of the lithium-carbon composite material, in the carbon sintered porous skeleton, the silver wire is entangled by the carbon nanotubes and is interspersed in the carbon sintered porous skeleton.
[0081] Preferably, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g. In addition, preferably, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0082] According to the technical solution of the present invention, the lithium-carbon composite material can be used as a negative electrode of a lithium-ion battery. Preferably, the lithium-carbon composite material has a sheet structure, and the thickness of the lithium-carbon composite material is in the range of 1 μm to 5 μm.
[0083] Preferably, in order to better achieve the mechanical and electrical effects of the lithium-carbon composite material described in detail above, the carbon nanotubes are multi-walled carbon nanotubes.
[0084] Preferably, the diameter of the carbon nanotube is in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and the length is in the range of 3 μm to 15 μm. Preferably, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm. Preferably, in order to obtain a structure in which the silver wire is wound by the carbon nanotube, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.3-1000.
[0085] Preferably, in order to better achieve the mechanical and electrical effects of the lithium-carbon composite material described in detail above, based on the weight of the lithium-carbon composite material as 100%, the weight of the carbon nanotubes accounts for 2-75% by weight, preferably 7-55% by weight, and more preferably 11-46% by weight; based on the weight of the lithium-carbon composite material as 100%, the weight of the silver wire accounts for 0.5-25% by weight, preferably 1.2-18% by weight, and more preferably 3.5-14.5% by weight; based on the weight of the lithium-carbon composite material as 100%, the weight of the lithium alloy accounts for 2-57% by weight, preferably 3.6-48% by weight, and more preferably 5.4-34.5% by weight; and based on the weight of the lithium-carbon composite material as 100%, the weight of the metallic lithium accounts for 2-95.5% by weight, preferably 10-87% by weight, and more preferably 21-75% by weight.
[0086] According to the technical solution of the present invention, the lithium alloy is a compound lithium alloy. Preferably, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0087] Preferably, the thickness of the negative electrode is in the range of 1 μm to 200 μm, preferably 1 μm to 5 μm.
[0088] According to another aspect of the present invention, a method for preparing an all-solid-state lithium metal battery is provided, the method comprising the following steps:
[0089] (a) dispersing carbon nanotubes, silver wires, a binder and a cross-linking agent in a solvent to prepare a dispersion;
[0090] (b) treating the dispersion at high temperature to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires;
[0091] (c) adding a lithium alloy to molten metallic lithium to prepare a lithium melt containing the lithium alloy;
[0092] (d) immersing the carbon sintered porous skeleton containing the carbon nanotubes and the silver wires into the lithium melt containing the lithium alloy, so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton;
[0093] (e) taking out the impregnated carbon sintered porous skeleton from the lithium melt, casting an ingot and cooling it to obtain a lithium-carbon composite material;
[0094] (f) processing the lithium-carbon composite material into a negative electrode; and
[0095] (g) assembling a positive electrode, a solid electrolyte and the negative electrode to obtain the metal lithium battery.
[0096] There is no particular restriction on the material used for the positive electrode of the present invention. Preferably, the positive electrode comprises one or more of an organic positive electrode material and an inorganic positive electrode material. The organic positive electrode material is selected from one or more of polypyrrole and its derivatives, polyacrylonitrile and its derivatives, and anthraquinone and its derivatives. The inorganic positive electrode material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobaltate, lithium manganate, lithium nickelate, lithium nickel manganate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, over-lithiated positive electrode, sulfur, carbon and oxygen.
[0097] Preferably, the solid electrolyte comprises one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte. Specific examples of the materials listed above can be commercially available or prepared according to known methods.
[0098] Optionally, the all-solid-state lithium metal battery further comprises packaging materials, and the packaging method is at least one of a soft-pack battery, a cylindrical battery or a steel-shell battery.
[0099] Preferably, in order to better achieve the mechanical and electrical effects of the lithium-carbon composite material described in detail above, the carbon nanotubes are multi-walled carbon nanotubes.
[0100] Preferably, the diameter of the carbon nanotube is in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and the length is in the range of 3 μm to 15 μm. Preferably, the diameter of the silver wire is in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and the length is in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm. Preferably, in order to obtain a structure in which the silver wire is wound by the carbon nanotube, the ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000.
[0101] There is no particular restriction on the specific type of the binder that can be used in the present invention. Preferably, the binder is selected from one or more of polyvinyl alcohol, polyvinylidene fluoride, polybutylene styrene, polystyrene, polycarboxyl cellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and its derivatives, monosaccharide or polysaccharide polymers.
[0102] There is no particular limitation on the specific type of cross-linking agent that can be used in the present invention. Preferably, the cross-linking agent is selected from one or more of carbomer, benzoyl peroxide, diethylenetriamine, hydrated sodium borate, cellulose derivatives and isothiazolinone.
[0103] There is no particular restriction on the specific type of the solvent that can be used in the present invention. Preferably, the solvent is selected from one or more of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, lemon essence, alcohol, xylene, toluene cyclohexanone, isopropyl alcohol, ether, propylene oxide, methyl butyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol and ethylenediamine.
[0104] Preferably, the high temperature treatment comprises heating the dispersion at a temperature of 350° C. to 800° C. for 1 to 5 hours.
[0105] Preferably, the temperature of the molten metallic lithium is in the range of 200°C to 2500°C.
[0106] Preferably, the lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy.
[0107] Preferably, in step (a), the weight ratio of the binder, the cross-linking agent and the carbon nanotubes is (5-65): (2-25): (10-93).
[0108] Preferably, in the carbon sintered porous skeleton, the silver wires are entangled by the carbon nanotubes and are interspersed in the carbon sintered porous skeleton.
[0109] Preferably, the pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g. In addition, preferably, the porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%.
[0110] Preferably, the thickness of the negative electrode is in the range of 1 μm to 200 μm, preferably 1 μm to 5 μm.
[0111] Preferably, step (f) comprises subjecting the lithium-carbon composite material to at least one of cutting, melt coating, extrusion, flat pressing, rolling, and low-temperature crushing.
[0112] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0113] Example
[0114] In the present invention, unless otherwise specified, the reagents used are commercial products and are used directly without further purification. In addition, the "%" mentioned is "% by weight", and the "parts" mentioned are "parts by weight".
[0115] Test Method
[0116] According to the test methods described in detail below, the negative electrode materials prepared in the following embodiments and comparative examples were subjected to structural strength tests and the metal lithium batteries prepared therefrom were subjected to electrical performance (battery cycle) tests.
[0117] Structural strength test
[0118] The negative electrode sheets prepared in the following examples and comparative examples were cut into test strips, the strip size was: 87.5 mm long × 12.5 mm wide, three strips were cut from each material, and the tensile test was performed on a tensile test equipment (model BT series, manufacturer Shenzhen Beite Instrument Equipment Co., Ltd.). Specifically, the test steps refer to "GB-228-87 Metal Tensile Test Method". The results are shown in the following Table 1.
[0119] Battery cycle test
[0120] The negative electrode sheets prepared in the following examples and comparative examples were used as negative electrodes to prepare all-solid-state metal lithium batteries, and the assembled all-solid-state metal lithium batteries were subjected to charge-discharge tests. The charge-discharge current was 2 mA, the charge-discharge time was 1 hour, and the cycle was continued until the battery life ended. The charge-discharge times were recorded. The test results are displayed in Figure 3 .
[0121] Example 1
[0122] Carbon nanotubes (GTC-304 purchased from Shandong Dazhan Nanomaterial Co., Ltd., with a diameter of 15-25 nm and a length of 5-15 μm), silver wires (silver wires purchased from Suzhou Nofei Nanotechnology Co., Ltd., with a diameter of 80 nm and a length of 73.5 μm), a binder polyvinyl alcohol and a cross-linking agent benzoyl peroxide were dispersed in deionized water to prepare a dispersion, wherein the weight ratio of the carbon nanotubes, the silver wires, the binder and the cross-linking agent was 9:4.5:0.5:1.
[0123] The dispersion is placed in an inert atmosphere protection furnace for high temperature treatment (treatment temperature is 500° C., treatment time is 2 hours) to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires. Figure 1 The scanning tunneling microscope (SEM) image of the carbon sintered porous framework containing carbon nanotubes and silver wires prepared in Example 1 of the present invention is shown. Figure 1 It can be seen that the silver wire with a diameter of 80nm runs through the carbon sintered porous skeleton, the surface of the silver wire is rough, and carbon nanotubes are entangled.
[0124] Furthermore, a lithium aluminum alloy (lithium and aluminum element mass ratio of 4:1) was added to the molten metal lithium at a temperature of 800° C. while stirring to prepare a lithium melt containing the lithium alloy.
[0125] The carbon sintered porous skeleton containing the carbon nanotubes and the silver wires is immersed in the lithium melt containing the lithium alloy so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton. Subsequently, the impregnated carbon sintered porous skeleton is taken out from the lithium melt, cast into an ingot, and cooled to obtain a lithium-carbon composite material. Figure 2 The scanning tunneling microscope (SEM) photo of the lithium-carbon composite material prepared in Example 1 of the present invention is shown. Figure 2 It can be seen that a small amount of carbon nanotube skeleton is exposed on the surface of the lithium-carbon composite material, and part of the voids in the carbon nanotube skeleton are filled with metallic lithium and lithium aluminum alloy. EDX energy spectrum analysis of the specific structure of the lithium-carbon composite material proves that lithium alloy and metallic lithium exist simultaneously in the voids of the carbon sintered porous skeleton.
[0126] The lithium-carbon composite material is used to prepare a lithium-carbon composite sheet with a thickness of 50 microns through extrusion and rolling.
[0127] According to the structural strength test method described in detail above, the obtained lithium-carbon composite sheet was subjected to a structural strength test, and the results are shown in Table 1 below.
[0128] In addition, the positive electrode, solid electrolyte and negative electrode are assembled into a metal lithium soft pack battery, wherein: the negative electrode is a lithium carbon composite sheet prepared as above; the positive electrode adopts a high nickel ternary positive electrode material (NCM811); the solid electrolyte is a sulfide solid electrolyte (Li 11 Ge2PS 12 ).
[0129] According to the battery cycle test method described in detail above, the obtained all-solid-state metal lithium soft-pack battery was subjected to a battery cycle test, and the results showed that Figure 3 middle.
[0130] Example 2
[0131] A lithium carbon composite sheet was prepared in a similar manner to Example 1, except that the lithium aluminum alloy was replaced with a lithium indium alloy (the element mass ratio of lithium to indium was 4:1). According to the structural strength test method described in detail above, the obtained lithium carbon composite sheet was subjected to a structural strength test, and the results are shown in Table 1 below.
[0132] Example 3
[0133] A lithium-carbon composite sheet was prepared in a similar manner to Example 1, except that the lithium-aluminum alloy was replaced with a lithium-boron alloy (the element mass ratio of lithium to boron was 4:1). According to the structural strength test method described in detail above, the obtained lithium-carbon composite sheet was subjected to a structural strength test, and the results are shown in Table 1 below.
[0134] Example 4
[0135] A lithium carbon composite sheet was prepared in a similar manner to Example 1, except that the silver wire (a silver wire purchased from Suzhou Nofi Nanotechnology Co., Ltd., with a diameter of 80 nm and a length of 73.5 μm) was replaced with a silver wire (a silver wire purchased from MacLean Reagent Network, with a diameter of 3 μm and a length of 23 μm). The obtained lithium carbon composite sheet was subjected to a structural strength test according to the structural strength test method described in detail above, and the results are shown in Table 1 below.
[0136] Example 5
[0137] A lithium-carbon composite sheet and an all-solid-state lithium metal soft-pack battery were prepared in a manner similar to Example 1, except that a halide solid electrolyte (Li3YCl6) was used instead of a sulfide solid electrolyte (Li 11 Ge2PS 12 ). According to the battery cycle test method described in detail above, the obtained all-solid-state metal lithium soft-pack battery was subjected to a battery cycle test. The results show that the all-solid-state metal lithium soft-pack battery prepared in Example 5 has good battery cycle performance similar to that of the all-solid-state metal lithium soft-pack battery prepared in Example 1.
[0138] Example 6
[0139] A lithium-carbon composite sheet and an all-solid-state lithium metal soft-pack battery were prepared in a similar manner to Example 1, except that Li6PS5Cl was used instead of the sulfide solid electrolyte (Li 11 Ge2PS 12 ). According to the battery cycle test method described in detail above, the obtained metal lithium soft pack battery was subjected to a battery cycle test. The results showed that the metal lithium soft pack battery prepared in Example 6 had good battery cycle performance similar to that of the all-solid-state metal lithium soft pack battery prepared in Example 1.
[0140] Example 7
[0141] A lithium-carbon composite sheet and an all-solid-state lithium metal soft-pack battery were prepared in a similar manner to Example 1, except that Li7La3Zr2O 12 Replace sulfide solid electrolyte (Li 11 Ge2PS 12 ). According to the battery cycle test method described in detail above, the obtained metal lithium soft pack battery was subjected to a battery cycle test. The results showed that the metal lithium soft pack battery prepared in Example 7 had good battery cycle performance similar to that of the all-solid-state metal lithium soft pack battery prepared in Example 1.
[0142] Example 8
[0143] A lithium-carbon composite sheet and an all-solid-state lithium metal soft-pack battery were prepared in a similar manner to Example 1, except that polyethylene oxide (PEO, average molecular weight 1.2 million) and Li7La3Zr2O 12 The organic-inorganic composite solid electrolyte replaces the sulfide solid electrolyte (Li 11 Ge2PS 12 ). According to the battery cycle test method described in detail above, the obtained all-solid-state metal lithium soft-pack battery was subjected to a battery cycle test. The results showed that the metal lithium soft-pack battery prepared in Example 8 had good battery cycle performance similar to that of the all-solid-state metal lithium soft-pack battery prepared in Example 1.
[0144] Example 9
[0145] A lithium-carbon composite sheet and an all-solid-state metal lithium soft-pack battery were prepared in a manner similar to that of Example 1, except that a steel shell was used as the packaging material. According to the battery cycle test method described in detail above, the obtained all-solid-state metal lithium soft-pack battery was subjected to a battery cycle test. The results showed that the metal lithium soft-pack battery prepared in Example 9 had good battery cycle performance similar to that of the all-solid-state metal lithium soft-pack battery prepared in Example 1.
[0146] Comparative Example 1
[0147] A lithium carbon composite sheet was prepared in a similar manner to Example 1, except that no silver wire was used in the preparation. According to the structural strength test method described in detail above, the obtained lithium carbon composite sheet was subjected to a structural strength test, and the results are shown in Table 1 below.
[0148] Comparative Example 2
[0149] A lithium-carbon composite sheet was prepared in a similar manner to Example 1, except that no lithium-aluminum alloy was used in the preparation, and only molten metallic lithium was used to impregnate the carbon sintered porous framework. The obtained lithium-carbon composite sheet was subjected to a structural strength test according to the structural strength test method described in detail above.
[0150] Comparative Example 3
[0151] The structural strength test described in detail above was carried out using a commercial pure lithium ribbon with a thickness of 50 microns, and the results are shown in the following Table 1. In addition, the commercial pure lithium ribbon with a thickness of 50 microns was used as the negative electrode to prepare an all-solid-state metal lithium soft-pack battery in a manner similar to Example 1. According to the battery cycle test method described in detail above, the obtained all-solid-state metal lithium soft-pack battery was subjected to a battery cycle test, and the results are shown in Figure 3 middle.
[0152] Table 1 Tensile test results of materials of Examples 1-4 and Comparative Examples 1-3
[0153]
[0154] It can be seen from the above table that the pure metal lithium belt used in Comparative Example 3 has a larger elongation distance under a smaller tensile force, and the pure metal lithium belt has weak tensile strength. After adding nano silver wire to the pure metal lithium belt or replacing the pure metal lithium belt with lithium alloy, that is, Comparative Example 2 and Comparative Example 1, a larger tensile force is required to break the material. The present invention uses a combination of lithium alloy and silver wire, that is, Examples 1-4, which have a greater tensile strength. During the tensile test, the material can only be broken under a larger tensile force.
[0155] Figure 3 The cycle curves of the all-solid-state lithium metal soft-pack batteries prepared in Example 1 and Comparative Example 3 of the present invention are shown. Figure 3 It can be seen that the discharge capacity of the all-solid-state metal lithium battery in Example 1 begins to decay at 95 cycles. Figure 3 It is proved that the metal lithium soft pack battery of Example 1 has excellent battery cycle performance. On the other hand, the discharge capacity of the all-solid-state metal lithium battery in Comparative Example 3 begins to decay at about 48 weeks, and the cycle life of the all-solid-state battery of Example 1 is even close to twice that of the all-solid-state battery of Comparative Example 3.
[0156] Obviously, those skilled in the art can make various changes and modifications to the present disclosure without departing from the spirit and scope of the present disclosure. Thus, if these modifications and variations of the present disclosure fall within the scope of the claims of the present invention and their equivalents, the present disclosure is also intended to include these modifications and variations.
Claims
1. An all-solid-state metal lithium battery, the all-solid-state metal lithium battery comprising: positive electrode; Solid electrolytes; and The negative electrode is composed of a lithium-carbon composite material, which includes a carbon sintered porous skeleton containing carbon nanotubes and silver wires, wherein the gaps in the carbon sintered porous skeleton are filled with lithium alloy and metallic lithium.
2. The all-solid-state metal lithium battery according to claim 1, wherein the positive electrode comprises one or more of an organic positive electrode material and an inorganic positive electrode material, Preferably, the organic cathode material is selected from one or more of polypyrrole and its derivatives, polyacrylonitrile and its derivatives, and anthraquinone and its derivatives. Preferably, the inorganic positive electrode material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, over-lithiated positive electrode, sulfur, carbon and oxygen.
3. The all-solid-state metal lithium battery according to claim 1, wherein the solid electrolyte comprises one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.
4. The all-solid-state metal lithium battery according to claim 1, wherein the all-solid-state metal lithium battery satisfies one or more of the following items: The all-solid-state metal lithium battery further includes packaging materials; and The all-solid-state metal lithium battery is a soft-pack battery, a cylindrical battery or a steel-shell battery.
5. The all-solid-state metal lithium battery according to claim 1, wherein the all-solid-state metal lithium battery satisfies one or more of the following items: The silver wire is entangled by the carbon nanotubes and interspersed in the carbon sintered porous framework; The pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g; The porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%; The carbon nanotubes are multi-walled carbon nanotubes; The carbon nanotubes have a diameter in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and a length in the range of 3 μm to 15 μm; The silver wire has a diameter in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and a length in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm; The ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000; Based on the weight of the lithium-carbon composite material being 100%, the weight of the carbon nanotubes accounts for 2-75 weight %, preferably 7-55 weight %, and more preferably 11-46 weight %; Based on the weight of the lithium-carbon composite material being 100%, the weight of the silver wire accounts for 0.5-25 weight %, preferably 1.2-18 weight %, and more preferably 3.5-14.5 weight %; Based on the weight of the lithium-carbon composite material being 100%, the weight of the lithium alloy accounts for 2-57 weight %, preferably 3.6-48 weight %, and more preferably 5.4-34.5 weight %; Based on the weight of the lithium-carbon composite material being 100%, the weight of the metallic lithium accounts for 2-95.5 weight%, preferably 10-87 weight%, and more preferably 21-75 weight%; The lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy; and The thickness of the negative electrode is in the range of 1 μm to 200 μm, preferably 1 μm to 5 μm.
6. A method for preparing an all-solid-state metal lithium battery, the method comprising the following steps: (a) dispersing carbon nanotubes, silver wires, a binder and a cross-linking agent in a solvent to prepare a dispersion; (b) treating the dispersion at high temperature to prepare a carbon sintered porous framework containing the carbon nanotubes and the silver wires; (c) adding a lithium alloy to molten metallic lithium to prepare a lithium melt containing the lithium alloy; (d) immersing the carbon sintered porous skeleton containing the carbon nanotubes and the silver wires into the lithium melt containing the lithium alloy, so that the lithium melt containing the lithium alloy enters the voids of the carbon sintered porous skeleton; (e) taking out the impregnated carbon sintered porous skeleton from the lithium melt, casting an ingot and cooling it to obtain a lithium-carbon composite material; (f) processing the lithium-carbon composite material into a negative electrode; and (g) assembling a positive electrode, a solid electrolyte and the negative electrode to obtain the metal lithium battery.
7. The method for preparing an all-solid-state metal lithium battery according to claim 6, wherein the positive electrode comprises one or more of an organic positive electrode material and an inorganic positive electrode material, Preferably, the organic cathode material is selected from one or more of polypyrrole and its derivatives, polyacrylonitrile and its derivatives, and anthraquinone and its derivatives. Preferably, the inorganic positive electrode material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, over-lithiated positive electrode, sulfur, carbon and oxygen.
8. The method for preparing an all-solid-state metal lithium battery according to claim 6, wherein the solid electrolyte comprises one or more of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.
9. The method for preparing an all-solid-state metal lithium battery according to claim 6, wherein the method for preparing an all-solid-state metal lithium battery satisfies one or more of the following items: The carbon nanotubes are multi-walled carbon nanotubes; The carbon nanotubes have a diameter in the range of 1 nm to 100 nm, preferably 5 nm to 65 nm, more preferably 7 nm to 48 nm, and a length in the range of 3 μm to 15 μm; The silver wire has a diameter in the range of 10 nm to 100 μm, preferably 30 nm to 50 μm, more preferably 50 nm to 15 μm, and a length in the range of 5 μm to 100 μm, preferably 6 μm to 85 μm, more preferably 15 μm to 65 μm; The ratio between the diameter of the silver wire and the diameter of the carbon nanotube is in the range of 1.5-1000; The binder is selected from one or more of polyvinyl alcohol, polyvinylidene fluoride, polybutylene styrene, polystyrene, polycarboxycellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organic fluorine polymer, organic siloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerol, ethyl hydroxybenzoate and its derivatives, monosaccharide or polysaccharide polymers; The cross-linking agent is selected from one or more of carbomer, benzoyl peroxide, diethylenetriamine, hydrated sodium borate, cellulose derivatives and isothiazolinone; The solvent is selected from one or more of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, lemon essence, alcohol, xylene, toluene cyclohexanone, isopropanol, ether, propylene oxide, methyl butyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol and ethylenediamine; The high temperature treatment comprises heating the dispersion at a temperature of 350° C. to 800° C. for 1 to 5 hours; The temperature of the molten lithium metal is in the range of 200°C to 2500°C; The lithium alloy is selected from one or more of lithium aluminum alloy, lithium gold alloy, lithium barium alloy, lithium bismuth alloy, lithium calcium alloy, lithium gallium alloy, lithium germanium alloy, lithium indium alloy, lithium platinum alloy, lithium tin alloy, lithium zinc alloy, lithium lead alloy, lithium antimony alloy and lithium boron alloy; In step (a), the weight ratio of the binder, the crosslinking agent and the carbon nanotubes is (5-65):(2-25):(10-93); In the carbon sintered porous framework, the silver wire is entangled by the carbon nanotubes and is interspersed in the carbon sintered porous framework; The pore volume of the lithium-carbon composite material is in the range of 0.5 ml / g-3.5 ml / g, preferably 0.9 ml / g-2.5 ml / g; The porosity of the lithium-carbon composite material is in the range of 13.5%-89%, preferably 25%-78%; and The thickness of the negative electrode is in the range of 1 μm to 200 μm, preferably 1 μm to 5 μm.
10. The method for preparing an all-solid-state metal lithium battery according to claim 6, wherein step (f) comprises subjecting the lithium-carbon composite material to at least one of cutting, melt coating, extrusion, flat pressing, rolling, and low-temperature crushing.
Citation Information
Cited By
Lithium deposition redirection mixed conductor layer, preparation method thereof and lithium metal battery
CN122599439A